How Does it Feel? Factors Predicting Emotions and Perceptions Towards Sexual Harassment - Cojocaru, Lutzy (2022)
The present research addresses the effect of different variables on emotions and on perceptions held by research participants vis-à-vis situations that could be construed as sexual harassment. A total of 833 Israeli students participated in the study and use was made of a Sexual Harassment Definition Questionnaire (SHDQ). It was found that emotions aroused due to behaviour that is perceived as sexual harassment depend on variables such as age and gender of perpetrator and victim. More negative feelings were identified towards behaviours suggestive of sexual harassment among women than men, and among younger than older individuals, principally in situations where the perpetrator is a man. Situations in which the perpetrator and the victim were of the same gender were experienced as less flattering than those in which the gender was different. It was also found that women above the age of 40 perceived behaviour in which a woman related to a man or a woman in sexual terms as a situation with a higher potential for sexual harassment than one in which a man related to a woman or a man in a similar way. The findings show the extent to which social perceptions and emotions relating to sexual harassment are dynamic and context-dependent